Social Work in The Greek Schools: A Review of Policy Texts - Lempesi, Georgia Eleni (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Social work is an applied science that finds application in a multitude of fields, health, education, social protection, protection of the elderly, addiction, human rights, etc. Specifically, in the field of education both in America and in European countries, the social worker has an active presence in schools in various forms. This article will analyze the evolution of the role of the social worker in education in Greece through the study of the legislative framework from 1975 to 2018.